Effect of continuous ultrasonic irrigation on postoperative pain in mandibular molars with nonvital pulps: a randomized clinical trial. (28th June 2016) - Middha, M.; Sangwan, P.; Tewari, S.; Duhan, J.
Abstract: Aim: To evaluate via a randomized clinical trial the effect of continuous ultrasonic irrigation (CUI) on postoperative pain in mandibular molars with nonvital pulps. Methodology: Seventy mandibular molars with nonvital pulps and apical periodontitis were treated endodontically using two different irrigation techniques. The patients were randomly allocated to one of two groups, CUI ( n  = 35) and syringe irrigation (SI) ( n  = 35). The CUI group received irrigant activation using a Proultra Piezoflow ultrasonic needle as the final irrigation protocol, whilst in the SI group, the final irrigation was performed using 27‐gauge needle. All the patients were prescribed ibuprofen 400 mg to be taken every 8 h, if required. Postoperative pain using a visual analog scale and analgesic intake were recorded everyday for 7 days. Data were analysed using chi–Square, Mann–Whitney and multiple linear regression tests. Results: Mean postoperative pain was lower in the CUI as compared to SI group, but the difference was significant on the first day only ( P  = 0.032). The overall 24‐h pain prevalence was 41.4%. CUI had a lower incidence of pain (31.4%) as compared to the SI group (51.4%), but the difference was not significant ( P  > 0.05). No significant difference was observed in analgesic consumption between the groups ( P  > 0.05). Regression analysis revealed a significant association of mean postoperative pain at 24 h with the irrigant protocol ( P  = 0.017) and preoperative pain ( P  = 0.000). Conclusion: A significant difference was observed between CUI and syringe irrigation on the first postoperative day following chemo‐mechanical preparation. However, the benefit observed was not clinically relevant.